The Experience of People with Dementia and their Caregivers During Acute Hospitalization - Lemay, Genevieve (Université d'Ottawa / University of Ottawa, 2014)
Background: Due to the growing number of individuals suffering from dementia, many will require acute hospital care as other indirectly related conditions appear throughout the course of the disorder. Significant concerns have been raised about the provision of quality care. Understanding their experiences is essential. Method: Semi-structured interviews were conducted with caregivers and people with dementia after acute hospitalization. Data was analyzed using qualitative content analysis. Results: Twenty-nine participants experienced hospitalization and commented primarily on the negative experience. Despite the importance of caregiver involvement, and evidence of caregiver burden, they commented they were rarely included in care plans and lacked support. Continuity of care was said to be affected by absent communication amongst health care team members. The acute hospital process and environment was perceived as not supportive of dementia person-centred care principles, with reports of poor staff knowledge and recognition of the disorder. Conclusion: Reports of acute care hospital experiences of people with dementia and their caregivers provide insights for potential gaps in care delivery.
Keywords: Dementia; Caregivers; Acute Hospital; Patient Experience